State-Feedback Stabilization for Stochastic High-Order Nonlinear Systems with Time-Varying Delays - Fangzheng Gao; Zheng Yuan; Fushun Yuan (Abstract and Applied Analysis)
This paper investigates the problem of state-feedback stabilization for a class of stochastic high-order nonlinear systems with time-varying delays. Under the weaker conditions on the power order and the nonlinear growth, by using the method of adding a power integrator, a state-feedback controller is successfully designed, and the global asymptotic stability in the probability of the resulting closed-loop system is proven with the help of an appropriate Lyapunov-Krasovskii functional. A simulation example is given to demonstrate the effectiveness of the proposed design procedure.